Work Ability Index of Nurses in Different Departments of the Hospital - mahdieh rastimehr; adel mazloomi; Zeinab Kazemi (Muhandisī-i bihdāsht-i ḥirfah/ī)
Background and Objective: Due to the nature of shift work, nurses are under high stress, which can ultimately affect their work ability (WA). Considering the importance of the nursing profession, in this study, the work ability index (WAI) of nurses was investigated in different departments in one of the hospitals affiliated with Isfahan University of Medical Sciences. Materials and Methods: The present study is descriptive and analytical. The Work Ability Index questionnaire was used to evaluate work ability. First, 100 nurses were selected, and the collected data were analyzed in SPSS software (version 23) using descriptive and analytical statistical tests. Results: In this study, 45%, 32%, 16%, and 7% of individuals had average, good, excellent, and poor WA, respectively. The mean WAI was higher in single people than in married ones (P=0.032). The WAI of nurses was statistically significant according to their employment status (P=0.01). There was no significant difference between the WAI based on the type of department (P=0.224). Likewise, the WAI was lower in nurses who had a second job (P=0.04). Day-shift nurses had a higher WAI (P=0.01). Conclusion: In general, the WA status of nurses was in the average range. Given the relationship between some individual variables and the WAI, it is essential to adjust individuals' responsibilities based on these correlations to improve this index.